Couple-based lifestyle intervention to prevent type 2 diabetes: protocol for a randomised pilot trial - Whitaker, Madelyn; Aguirre, Monique C; Gutierrez Chavez, Manuel; Beaulieu, Elizabeth; Arones, Yeny B; Gershenoff, Dana; Hinton, Kristie; Klein, Natalie; Munezerou Uwizeye, Jeanne; Napia, Eru; Ramos, Carmen; Tavake-Pasi, O Fahina; et al. (BMJ open, 2023)
IntroductionType 2 diabetes is prevalent among US adults. Lifestyle interventions that modify health behaviours prevent or delay progression to diabetes among individuals at high risk. Despite the well-documented influence of individuals’ social context on their health, evidence-based type 2 diabetes prevention interventions do not systematically incorporate participants’ romantic partners. Involving partners of individuals at high risk for type 2 diabetes in primary prevention may improve engagement and outcomes of programmes. The randomised pilot trial protocol described in this manuscript will evaluate a couple-based lifestyle intervention to prevent type 2 diabetes. The objective of the trial is to describe the feasibility of the couple-based intervention and the study protocol to guide planning of a definitive randomised clinical trial (RCT).Methods and analysisWe used community-based participatory research principles to adapt an individual diabetes prevention curriculum for delivery to couples. This parallel two-arm pilot study will include 12 romantic couples in which at least one partner (ie, ‘target individual’) is at risk for type 2 diabetes. Couples will be randomised to either the 2021 version of the CDC’s PreventT2 curriculum designed for delivery to individuals (six couples), or PreventT2 Together, the adapted couple-based curriculum (six couples). Participants and interventionists will be unblinded, but research nurses collecting data will be blinded to treatment allocation. Feasibility of the couple-based intervention and the study protocol will be assessed using both quantitative and qualitative measures.Ethics and disseminationThis study has been approved by the University of Utah IRB (#143079). Findings will be shared with researchers through publications and presentations. We will collaborate with community partners to determine the optimal strategy for communicating findings to community members. Results will inform a subsequent definitive RCT.Trial registration numberNCT05695170